Estudo etnofarmacológico de plantas medicinais utilizadas em assentamentos rurais da cidade de Água Boa-MT: uma ferramenta para a saúde pública - Braz, Thiago [UNIFESP] (2013)
The use of herbal medicine is a technique historically spread by rural populations. It implicates multifactorial phenomena, such as the proximity and the availability of the natural resources, the belief in the therapeutic effect of species and the health care supply in different parts of the country. In this context, ethnopharmacology is a relevant tool in quest of this knowledge, particularly in areas with high levels of endemism of species, like the Brazilian Cerrado (savannah). This work, divided in two chapters, aimed (1) to identify herbal medicine species used in rural settlements and the development of these studies in the Brazilian public health field; (2) the sociocultural and environmental factors that affect the selection and the use of medicinal plants by inhabitants of rural settlements, in an effort to obtain a comprehensive overview about this popular practice. It is clear that the identification of the popular knowledge about medicinal species associated to the awareness about sociocultural and environmental factors related to this practice may contribute to the development of public policies about herbal medicine and phytotherapy.